How Prevalent Are Autistic Traits Among Children With Attention-Deficit/Hyperactivity Disorder? A Qualitative Review of the Literature - Uchida, Mai; Faraone, Stephen V.; Joshi, Gagan; Spencer, Andrea; Kenworthy, Tara; Woodworth, K Yvonne; Biederman, Joseph (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2013)
Background: Twin, family, and linkage studies have indicated that attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASDs) share a portion of their heritable etiology. This suggests that individuals with ADHD may manifest different forms of ASDs that may range from fully developed syndromic forms of the disorder to milder manifestations of ASD symptomatology, which will henceforth be referred to as autistic traits. Objective: The main purpose of this study was to conduct a literature search to examine the current body of knowledge regarding the prevalence of autistic traits (operationalized as the presence of autistic symptoms in the absence of a diagnosis of ASD) among children with ADHD and the associated morbidity of such traits. Method: A systematic literature search in PubMed was conducted to discover all controlled studies published in the English language that systematically assessed the presence of autistic traits in children with ADHD who did not meet the criteria for ASDs. Three articles met our inclusion and exclusion criteria and were included in this qualitative review. Results: Only three scientific papers that met our a priori inclusion and exclusion criteria were identified. These articles described findings obtained from clinical samples and identified a prevalence of autistic traits among children with ADHD that ranged from 7% to 60%. As compared with children with ADHD without these traits, the presence of autistic traits in children with ADHD was associated with more severe dysfunction in a wide range of non-overlapping domains and in the social and communication domains in particular. Conclusions: Although this study was limited by the small amount of available literature about this subject, these findings suggest that a sizeable subset of children with ADHD manifest autistic traits and that the presence of these traits is associated with increased dysfunction and social and communication deficits.